Ecological-health risks of potentially toxic metals in mangrove sediments near estuaries after years of piggery farming bans in Peninsular Malaysia - Chee, Kong Yap; Al-Mutairi, Khalid Awadh (MDPI, 2022)
The Sepang Besar River (SBR) was reported to be highly contaminated with Cu and Zn due to piggery farming wastes before 1998. Following the piggery farming ban (PFB) in 1998 in Bukit Pelanduk, the present study aimed to assess the ecological-health risks of potentially toxic metals (PTMs) (Cu, Pb, and Zn) in the mangrove surface sediments from SBR. Two adjacent rivers, namely the Sepang Kecil River and Lukut River, were also included for comparison purposes. The PTMs of present sediment samples collected in 2007 and 2010 were compared with those reported before and after PFB. The PTMs levels were lower than those of established sediment quality guidelines. Results of bioavailable fractions, individual contamination factor, risk assessment code, potentially ecological risk index (PERI), and non-carcinogenic risk (with HI < 1.0 based on the pathways of Cu, Pb, and Zn and the order: ingestion > dermal contact > inhalation), the present findings indicated that the three rivers had caused no ecological-health risks of Cu, Pb, and Zn. In particular, SBR estuary had drastic lower levels of Zn (7.48–9.40 times lower between 1998 and 2010) and Cu (8.30–36.9 times lower between 1998 and 2010), after 12 years of PFB. Based on the exponential decay model, the PERI values showed that the estuary of SBR has been improved from a “considerable ecological risk” to a “minimal ecological risk” after 12 years of PFB. This is the first paper on the ecological-health risks of Cu, Pb, and Zn in the estuary of SBR. Future monitoring is still necessary for effective risk management of the mangrove ecosystem at SBR.